Problemy strefy Euro - Balcerowicz, Leszek (Wydział Prawa i Administracji UAM, 2012)
Oficjalne kredyty ratunkowe dla niektórych krajów w strefie euro nie mogą zastąpić tam reform, które – poprawiając sytuację gospodarczą – pozwolą odzyskać owym krajom zaufanie rynków finansowych. W literaturze wymienia się dwie główne strukturalne słabości wspólnej waluty (euro): 1. Jednolita polityka pieniądza nie jest w stanie uwzględnić odmienności sytuacji poszczególnych krajów, a wspólny pieniądz nie pozwala na dewaluację w obrębie strefy euro; 2. Strefa euro istnieje bez „unii politycznej”. Artykuł analizuje zasadność tych tez.

The official rescue loans recently granted to a number of the Eurozone states cannot be treated as being in lieu of reforms that must be implemented in those countries in order to improve their economy, which they need so much to regain confidence of financial markets. There are two major structural weaknesses of the single currency (Euro) identified in literature: (i) the uniform monetary policy is incapable of accounting for differences among individual member states and single currency renders devaluation in Eurozone impossible; (ii) the eurozone exists without the ‘political union.’ The paper contains an analysis of the legitimacy of both theses.
Problems of Eurozone
Keywords: strefa euro; eurozone; gospodarka; economy; wspólna waluta; single currency; dewaluacja; devaluation; unia polityczna; political union